Overview of the recent research on the J-TEXT tokamak. (27th March 2015) - Zhuang, G.; Gentle, K.W.; Diamond, Patrick; Chen, J.; Rao, B.; Wang, L.; Zhao, Kaijun; Han, Sanghee; Shi, Yuejiang; Ding, Y.H.; Chen, Z.Y.; Hu, X.W.; et al.
Abstract: The experimental research over last two years on the J-TEXT tokamak is summarized and presented in the paper. The high-performance polarimeter-interferometer developed on J-TEXT, aiming to measure electron density and Faraday angle simultaneously, has time response up to 1  µ s, phase resolution <0.1° and spatial resolution ∼3 cm. Such high resolution permits investigations of fast equilibrium dynamics as well as magnetic and density perturbations associated with magnetohydrodynamic instabilities. Particle transport due to the sawtooth crashes is analysed. The sawteeth only partially flatten the core density profile and recovery between crashes implies an inward pinch velocity extending to the centre. The resonant magnetic perturbation (RMP) system on J-TEXT can generate a rotating helical field perturbation with a maximum rotation frequency up to 6 kHz, and dominant resonant modes of m / n  = 2/1, 3/1 or 1/1. It is found that tearing modes can be easily locked and then rotate together with a rotating RMP. The effects of RMPs on plasma flows and fluctuations are studied with Langmuir probe arrays at the plasma edge. The toroidal velocity increases and the radial electric field decreases with RMP coil current when the RMP current is no more than 5 kA. When the RMP current reaches 6 kA, the toroidal velocity profile becomes flattened near the last closed flux surface. The geodesic acoustic mode is damped in most of the edge region, while the low frequency zonal flow is damped inside the islands, but increases at its boundary.